CSA Practices for Sustainable Cocoa Farming Systems - Rubiano, Fernanda; Talsma, Tiffany; Nguyen Duy Nhiem; Nguyen-Duy, Nhiem (2018)
Climate change will shape the future production of cocoa and requires mutual cooperation amongst sector stakeholders to tailor responses to its differentiated impacts. Identifying and prioritizing climate smart agriculture (CSA) responses requires integration of multiple objectives and managing trade-offs between food security, adaptation and mitigation. Impact of future climates on growing regions is needed to select locally appropriate CSA practices. Zones of adaptation needs in Indonesia are identified and the ‘why?’ and ‘how?’ of tailored CSA practices are illustrated in an accessible guidebook format.